Enzymatic Transformation of Morphine by Hydroxysteroid Dehydrogenase from Pseudomonas testosteroni - Liras, Paloma (1975)
Enzyme preparations from Pseudomonas testosteroni containing α- and β-hydroxysteroid dehydrogenases catalyzed the oxidation of morphine and codeine by nicotinamide adenine dinucleotide. Morphine was converted in relatively low yield into 14-hydroxymorphinone probably via morphinone as an intermediate. Codeine was converted to codeinone and 14-hydroxycodeinone. Only the conversions at the 6-position were carried out by the hydroxysteroid dehydrogenase. Hydroxylation at the 14-position did occur spontaneously (or enzymatically with a contaminating enzyme) after oxidation at the 6-position.